MODERN LABORATORY DIAGNOSTICS OF NODULAR GOITER - Berdiyarova Shokhida Shukurullayevna; Najmiddinova Nigora Kamoliddinovna; Maksuddinova Munisa Shamsiddin kizi (TADQIQOTLAR.UZ, 2024)
Abstract: Nodular goiter is not just a physiological phenomenon, but a whole metaphor that  permeates the life  and being of  many people.  Its range  of  meanings ranges from purely medical aspects to deep philosophical reflections on existence. It seems to function in two planes: on the one hand, it is a manifestation associated with metabolic processes in the body, and on the other, it is a symbol of inner struggle and the search for harmony. In ancient texts, nodular goiter was often described through the prism of fear and misunderstanding.  People  who  faced  this  disease  felt  the  burden  of  prejudice  and superstition.  Over  time,  scientific  progress  has  made  it  possible  to  look  at  nodular goiter as a challenge that must be met with courage and knowledge.